EFFECTIVENESS OF BREASTFEEDING ANALGESIA AND HUGGING THERAPY ON PAIN RESPONSE DURING INFANT IMMUNIZATION - Mei Lia Nindya Zulis Windyarti; Nur Azizah; Siti Nur Umariyah Febriyanti; Dyah Ayu Wulandari (Universitas Karya Husada Semarang, 2025)
Background: The infant immunization program aims to ensure every infant receives complete basic immunization. Immunization is one of the main sources of pain and suffering that causes anxiety and trauma. Breastfeeding techniques and hugging therapy, which can be used as an alternative method to reduce pain in infants during injections (immunization). Research Objective: To determine the effectiveness of breastfeeding analgesia and hugging therapy on pain responses during infant immunization. Research Method: Quasi-experimental two-group post-test only design. The population in this study were all infants who underwent MR immunization totaling 68 infants. The sampling technique was purposive sampling with a sample size of 50 respondents. Instruments observation sheets FLACC. The analysis test used the independent t-test.Research Results: Pain response during infant immunization in the group given breastfeeding analgesia averaged 4.9. Pain response during infant immunization in the group given the hugging technique averaged 2.0. There was a difference in pain response during infant immunization between those given breastfeeding analgesia and hugging therapy with p-value = 0.007. Conclusion: hugging therapy is more effective than breastfeeding analgesia and on pain response during infant immunization